Shear‐Induced Orientation of Gyroid PS‐b‐P4VP(PDP) Supramolecules. Issue 15 (9th July 2013) - Vukovic, Ivana; Friedrich, Heiner; Merino, Daniel Hermida; Portale, Giuseppe; ten Brinke, Gerrit; Loos, Katja
<x xml:space="preserve">Abstract</x> The phase behavior of block copolymer based supramolecular complexes polystyrene‐block‐poly(4‐vinylpyridine) (PS‐b‐P4VP) and amphiphilic pentadecylphenol (PDP) molecules resembles the phase behavior of conventional block copolymers. Several PS‐b‐P4VP(PDP) complexes are found to self‐assemble into gyroid nanostructures. Typically, the grains are randomly oriented with a maximal size of several micrometers. Here, the orientation of a gyroid PS‐b‐P4VP(PDP) complex upon shearing is reported. It is found that the (111) gyroid lattice direction orients parallel to the shear direction after only several seconds of large amplitude oscillatory shearing. Oriented gyroid complexes can be used as templates for the preparation of metal nanofoams with improved ordering with potentially superior properties. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>